Integrasi Analisis Kebutuhan Dalam Strategi Pengembangan Bahan Ajar Bahasa Arab: Studi Pustaka - Nadia Ainun Nufus,; Sya’roni, Afaf; Fathul Maujud, (Journal of Arabic Education and Linguistics, 2025)
The development of relevant and contextual Arabic teaching materials requires the integration of needs analysis, encompassing linguistic, target, situational, and strategic dimensions. This study aims to formulate a strategic framework for developing Arabic teaching materials through a Systematic Literature Review based on the PRISMA 2020 guidelines, analyzing literature from Scopus, Google Scholar, and DOAJ databases for the period 2016–2025. The synthesis reveals that while needs analysis is recognized as crucial, its implementation remains partial, lacking comprehensive integration of the four dimensions and sufficient adaptation to local wisdom and digital technology. This study proposes an evidence-based integrative strategic model to enhance the effectiveness and relevance of Arabic language learning in Indonesia, emphasizing local context adaptation, digital media utilization, and diverse learning activities. These findings provide practical guidance for educators and curriculum developers to design teaching materials responsive to learners’ needs.